Acceptability, engagement, outcomes, and dose–response associations of a mindfulness-based meditation app in individuals waiting for psychological services - Alexander R. Daros; Alina Patel; Oghenetega Otevwe; Santiago Sotelo; Bechara J. Saab; Lena C. Quilty (BMC Digital Health)
Abstract Background While mindfulness apps have received growing clinical attention, their integration within health systems has received limited investigation. In this study, we evaluated a mindfulness app in adults waiting for psychological services. A non-randomized clinical trial was conducted with a 4-week intervention period and 8-week follow-up. At baseline, adults (N = 193) with moderate depression and anxiety symptoms completed an assessment and received access to a mobile mindfulness app called AmDTx. Additional assessments were completed at 2-, 4-, 8-, and 12-weeks post-baseline. Descriptive statistics of attrition, adoption, acceptability, and engagement were computed. Linear mixed models estimated treatment outcomes for functional disability (primary outcome), depression, anxiety, stress, rumination, and mindful awareness/acceptance. We also evaluated the dose–response association between app use and functional disability. Results Using intent-to-treat (ITT) analyses, there was a 75% adoption rate and a 30% attrition rate at post-treatment (i.e., 4 weeks post-baseline). In addition, 1.09 hours of meditation time and 9.16 exercises were recorded on average at post-treatment. During follow-up, less than a third of participants remained active users, but they reported increases in meditation hours and number of exercises. Participants reported positive ratings of credibility, acceptability, and usability ratings. Treatment effects were observed in the expected direction for all outcomes but one (mindful awareness). Dose-response relationships indicated that increases in app engagement correlated with decreases in functional disability Conclusions The findings reinforce the potential for AmDTx, and mindfulness apps more broadly, to serve as low-intensity tools to alleviate unmet service needs and impart clinically meaningful benefit for a significant subset of those waiting for psychological services. Trial registration ClinicalTrials.gov NCT05211960, Registered 2022–01-26.